Screening for antisocial personality disorder in drug users – a qualitative exploratory study on feasibility - Fischer, Benedikt (Int J Methods Psychiatr Res, 2006)
Knowledge about co‐occurring personality disorders in drug users is important for planning therapy and prevention. The objective of this study was to assess whether the SCID‐II (Structured Clinical Interview for DSM‐III‐R) Screen for antisocial personality disorder was feasible and acceptable in a population of opioid users. A qualitative study on veridicality and emotional quality in responses to SCID‐II Screen was carried out by personal interview in a multifunctional addiction centre. The subjects were 10 outpatient participants (six female, four male) in methadone substitution treatment. The SCID‐II Screen triggered a high level of emotions. Some questions were mainly interpreted from a victim's perspective, even though the intention was the perpetrator's view. Questions were seen as sex‐biased. Provision of support to deal with potential emotional problems should be supplied. Potential revision should be considered to include the female perspective in the screen. Copyright © 2003 Whurr Publishers Ltd.